STRATIGRAPHY AND PETROGRAPHY OF ROCKS IN KARANGTENGAH VILLAGE AND SURROUNDINGS, BABAKAN MADANG SUB-DISTRICT, BOGOR DISTRICT, WEST JAVA PROVINCE - GANI, REZA MOHAMMAD GANJAR; Firmansyah, Yusi; Putri, Nisrina Nadellia; Efendi, Tri Septianto; Fachrudin, Kurnia Arfiansyah (Faculty of Geological Engineering, Universitas Padjadjaran, 2023)
Stratigraphy and petrography, integral components of geological science, are crucial for identifying mineral composition, rock texture, and characteristics, as well as understanding relationships between layers and layer positions. This study is located in Karangtengah Village and its Nearby Surroundings, Babakan Madang District, Bogor Regency, West Java Province. Physiographically, the study area is included in the Bogor Zone (Van Bemmelen, 1949). The research site is also incorporated in the Geological Map of Bogor Sheet, West Java. And specifically this research was conducted in the Cileungsi River. This river is included in the Jatiluhur Formation (Sudjatmiko, 1972). Stating the purpose of geological mapping, such as understanding regional geology, identifying mineral resources, or assessing geological hazards. Then, data collection in the field, such as conducting detailed field surveys to observe and record geological features, using field notebooks, GPS for plotting, and cameras for documentation, collecting rock samples for laboratory analysis (Petrography analysis and microfossil analysis). As a result of this study, there are four rock units in the Karangtengah area, with the order of formation from the oldest to the youngest. Firstly, Claystone Unit (Tmbl) consists of mudstones and sandstones, with fossils of P. transitoria and G. peripheroronda indicating an Early Miocene age (N8) and the depositional environment is the Outer Neritic. Second, the Old Andesite Intrusion (At) consists of andesite igneous rocks with Middle Miocene age and deposited in a terrestrial environment. Third, the Tuff Unit (Qt) is dominated by pyroclastic tuff rocks with Pleistocene age and deposited in a terrestrial environment. Finally, the Andesite Unit (Am) consists of andesite igneous rocks younger than the Pleistocene, penetrating the Tuff Unit (Qt) and the Claystone Unit, and deposited in a terrestrial environment.